Analisis Kepemilikan Sertifikat Tanah terhadap Akses Pinjaman Rumah Tangga - Azzis, Abdul Azzis; Nuryakin, Chaikal (UI Scholars Hub, 2025)
This study aims to examine the impact of land certificate ownership on access to loans from formal financial institutions. Utilizing data from Indonesia in 2018, we employ logistic regression analysis to investigate the relationship between land certificate ownership and loan access in the country. The examination of land certification in relation to loan access, by distinguishing types of land ownership evidence and loan types, is deemed essential. The findings indicate that the impact of land certification is less effective for low-income households. Beyond ensuring accessible and affordable land certification processes, the government should formulate policies for innovative loan schemes, such as the use of social collateral, to enhance the bankability of this social group.